Engineering logic gates using synthetic SIRNAs in escherichia coli for gene silencing - Lim, Carol Yi Ting (2014)
Synthetic small interfering RNAs have generated large interest in both basic and applied biology due to their ability to knock down and silence the gene of interest. At the same time it also serves as a requisite tool to study genetic function in cells. To date, very little literature has been found which comprehensively incorporating siRNAs into all 16 logic gates hence the author aim to fill in this gap of information by introducing a new molecular mechanism to construct the siRNA based logic circuits.